Child and Adolescent Mental Health Policy in Low- and Middle-Income Countries: Challenges and Lessons for Policy Development and Implementation - Zhou, Wei; Ouyang, Feiyun; Nergui, Oyun-Erdene; Bangura, Joseph Benjamin; Acheampong, Kwabena; Massey, Isaac Yaw; Xiao, Shuiyuan (Frontiers in Psychiatry, 2020)
Background: Child and adolescent mental health (CAMH) policy is essential for the rational development of mental health systems for children and adolescents. However, there is a universal lack of CAMH policy, especially in low and middle income countries (LMICs). Therefore, this review aims to identify challenges and lessons for LMICs to develop and implement CAMH policy. Methods: PubMed (1781-), Medline (1950-), Embase (1966-) and PsychINFO (1895-) were searched from inception to 31 December 2018 for publications on CAMH policy development and/or implementation. Abstracts and main texts of papers were double screened, and extracted data were analyzed through thematic synthesis. Results: A total of 31 publications were included through the systematic review. Six major challenges were identified for CAMH policy in LMICs: (i) poor public awareness and low political willingness; (ii) stigma against mental disorders; (iii) biased culture values towards children and adolescents and CAMH, from developmental nihilism to medicalization; (iv) the lack of CAMH data and evidence, from service statistics to program evaluation; (v) the shortage of CAMH resources, including human resources, service facilities and funding; (vi) unintended consequence of international support, including reducing local responsibilities, planning fragmentation, and unsustainability. Six lessons to overcome challenges were summarized: (i) rethinking the concept of CAMH; (ii) encouraging a stand-alone CAMH policy and budget; (iii) involving stakeholders; (iv) reinforcing the role of research and researchers in policy process; (v) innovating the usage of human and service resources; (vi) maximizing the positive influence of international organizations and non-governmental organizations. Conclusion: LMICs are still facing many challenges for their CAMH policy development and implementation. To overcome the challenges, great and long-term efforts are needed, which include great determination of from domestic and global agents, multi-disciplinary innovations, and collaboration and coordination from different sectors.